Over one‐third of African‐American MGUS and multiple myeloma patients are carriers of hyperphosphorylated paratarg‐7, an autosomal dominantly inherited risk factor for MGUS/MM. Issue 4 (4th February 2014) - Zwick, Carsten; Held, Gerhard; Auth, Michaela; Bernal‐Mizrachi, Leon; Roback, John D.; Sunay, Susan; Iida, Shinsuke; Kuroda, Yoshiaki; Sakai, Akira; Ziepert, Marita; Ueda, Ryuzo; Pfreundschuh, Michael; et al.
<x xml:space="preserve">Abstract</x> As hyperphosphorylated paratarg‐7 (pP‐7) carrier state was shown to be the first molecularly defined autosomal dominantly inherited risk factor for monoclonal gammopathy of unknown significance (MGUS) and multiple myeloma (MM) in a European population, the prevalence of pP‐7 carrier state among African‐Americans who have a significantly higher incidence of MGUS/MM is of interest. We therefore determined pP‐7 carrier state and paraproteins with specificity for P‐7 in African‐American, European and Japanese patients with MGUS/MM and healthy controls. By isoelectric focusing and ELISA, a paratarg‐7‐specific paraprotein and the associated pP‐7 carrier state was observed in 30/81 (37.0%) African‐American, 42/252 (16.7%) European and 7/176 (4.0%) Japanese MGUS/MM patients (p < 0.001). A pP‐7 carrier state was found in 11/100 (11.0%) African‐American, 8/550 (1.5%) European and 1/278 (0.4%) Japanese healthy controls (p < 0.001), resulting in an odds ratio for MGUS/MM of 4.8 (p < 0.001) among African‐American, 13.6 among European (p < 0.001) and 11.5 (p = 0.023) among Japanese carriers of pP‐7. We conclude that pP‐7 carriers are most prevalent among African‐Americans, but a pP‐7 carrier state is the strongest molecularly defined single risk factor for MGUS/MM known to date in all three ethnic groups. The high prevalence of pP‐7 carriers among African‐American patients emphasizes a predominant role of this genetic factor in the pathogenesis of these diseases. The large number of pP7 African‐American patients and controls should facilitate the identification of the SNP or mutation underlying the pP‐7 carrier state.